A bismaleimide resin containing epoxidized polybutadiene chain segments and its preparation method and application
By developing bismaleimide resin containing epoxidized polybutadiene segments, the existing BMI resin has solved the problems of difficult processing, high cost and difficult curing reaction control, and the excellent stability and good mechanical properties of the resin at high temperatures have been achieved, and its application potential in the fields of new energy and biomedical materials has been expanded.
Patent Information
- Application Number
- CN202411855700.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing BMI resins have challenges in terms of difficult processing, high cost and difficult curing reaction control, and their application areas are limited, especially in new energy and biomedical materials.
A bismaleimide resin containing epoxidized polybutadiene segments is developed. The resin is liquid at room temperature, has better processability, and forms a three-dimensional network structure through thermal crosslinking, enhancing its mechanical properties and high temperature resistance.
The resin has excellent stability and chemical resistance at high temperatures, good mechanical properties and high temperature resistance, good processability at room temperature, and has broad application prospects.
Smart Images

Figure CN119306922B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a bismaleimide resin containing an epoxidized polybutadiene chain segment and a preparation method and application thereof. Background Art
[0002] BMI resin, or bismaleimide resin, is a type of high-performance thermosetting resin. It is widely used in aerospace, electrical and electronic, and automotive industries for its excellent heat resistance, excellent mechanical properties, and good chemical stability. In the field of high-performance composite materials, the performance of the resin matrix is crucial, which directly affects the final application of the composite material. As a special engineering plastic, BMI resin contains maleimide groups in its molecular structure, which can form a three-dimensional network structure through thermal curing, photocuring, or photothermal curing under heating conditions, thus providing a rich selection of molding processes, which can be used in adhesives, coatings, coatings, membrane manufacturing and other segmented applications.
[0003] BMI resin can withstand extreme temperature conditions after curing and maintain the physical properties of the material without degradation, which makes it have significant advantages in high temperature environment. Compared with traditional epoxy resin, BMI resin has a higher glass transition temperature (Tg) and better mechanical properties, such as tensile strength, impact strength and fatigue resistance. BMI resin has good resistance to a variety of chemicals, including hydrolysis resistance, acid and alkali resistance and organic solvent resistance, which enables it to maintain its performance in harsh chemical environments. With the development of science and technology and the increase in industrial demand, the application of BMI resin in the aerospace field is particularly prominent, such as for the manufacture of aircraft structural components and thermal protection systems. At the same time, it also shows great potential in the manufacture of insulating materials in the electronic and electrical fields and lightweight components in the automotive industry. Although BMI resin has many advantages, its high cost, difficulty in processing and control of curing reaction are still challenges in current research. In addition, the development of new BMI resin systems, the reduction of processing difficulty, the reduction of manufacturing costs, and the exploration of its new applications in new energy, biomedical materials and other fields are all important directions for future research. The research on BMI resins not only focuses on the synthesis and modification of materials, but also includes an in-depth understanding of the curing mechanism, innovation in processing technology, and performance optimization in specific application environments. With the continuous development of new BMI resins and the continuous expansion of application areas, research in this field will continue to contribute new impetus to the development of high-performance materials. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a bismaleimide resin containing an epoxidized polybutadiene segment and a preparation method and application thereof. The bismaleimide resin of the present invention is liquid at room temperature, giving it better processability, and is a high-performance BMI resin material.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] In one aspect, the present invention provides a bismaleimide resin having a structure as shown in Formula 1 below:
[0007]
[0008] Formula 1
[0009] Wherein, R1 is selected from C1-C5 alkylene, and the number average molecular weight of the bismaleimide resin is 2000g / mol-3000g / mol.
[0010] In the present invention, in the bismaleimide resin having the structure shown, two maleimide groups are distributed at both ends, the structure contains double bonds, and its saturation is relatively high. This gives the resin excellent stability and chemical resistance at high temperatures. During the hardening process, the BMI resin forms a three-dimensional network structure through thermal cross-linking, which enhances its mechanical properties and high temperature resistance. This cross-linked structure helps to improve the thermoplasticity of the resin.
[0011] Preferably, R1 is selected from CH2-, -CH2-CH2- or -CH2-CH2-CH2-CH2-CH2-CH2-.
[0012] Preferably, the bismaleimide resin has a number average molecular weight of 2000 g / mol-3000 g / mol, for example, 2000 g / mol, 2300 g / mol, 2500 g / mol, 2800 g / mol or 3000 g / mol.
[0013] Preferably, the bismaleimide resin is selected from any one of the following resins:
[0014] ;
[0015] .
[0016] On the other hand, the present invention provides a method for preparing the bismaleimide resin as described above, the preparation method comprising the following steps:
[0017] The compound represented by formula A reacts with the compound represented by formula B to obtain the bismaleimide resin represented by formula 1. The reaction formula is as follows:
[0018]
[0019] wherein R1 and n are defined in the same manner as in formula I.
[0020] Preferably, the molar ratio of the compound represented by formula A to the compound represented by formula B is 3:1-6:1, for example 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1.
[0021] Preferably, the reaction is carried out in the presence of a dehydrating agent.
[0022] Preferably, the molar ratio of the compound represented by formula A to the dehydrating agent is 1:1-1:2, for example, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.7, 1:1.8, 1:1.9 or 1:2.
[0023] Preferably, the dehydrating agent is selected from at least one of N,N'-dicyclohexylcarbodiimide (DCC), diisopropylcarbodiimide (DIC) or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI).
[0024] Preferably, the reaction is carried out in the presence of a catalyst.
[0025] Preferably, the catalyst is selected from at least one of 4-dimethylaminopyridine, 4-pyrrolidinylpyridine, hydroxybenzotriazole or diphenylamine trifluoromethanesulfonate.
[0026] Preferably, the molar ratio of the catalyst to the compound represented by formula B is 1:10-1:15, for example 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.
[0027] Preferably, the reaction temperature is room temperature (15-35°C, such as 15°C, 18°C, 20°C, 25°C, 28°C, 30°C, 33°C or 35°C) and the reaction time is 12-24h, such as 12h, 13h, 15h, 18h, 20h, 22h or 24h.
[0028] In another aspect, the present invention provides use of the bismaleimide resin described above in the preparation of a thermosetting material.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The bismaleimide resin of the invention has excellent stability and chemical resistance at high temperatures, good mechanical properties and high temperature resistance, is liquid at room temperature, has good processability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1Thermogravimetric analysis diagrams of BMI-PPG400, BMI-PPG1000 and BMI-600E. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0033] Preparation Example 1
[0034] Synthesis of bismaleimide resin:
[0035]
[0036] Dissolve maleimide propionic acid (253.5 g, 1.5 mol) in 2500 mL of dichloromethane, then dissolve dicyclohexylcarbodiimide (DCC) powder (309 g, 1.5 mol) in 300 mL of dichloromethane. Slowly drop the DCC solution into the maleimide propionic acid solution under stirring. After all the additions are completed, continue stirring and reacting for 10 min. Then add (epoxidized polybutadiene, Total) Polybd 600E (725 g, 0.5 mol) into the system; finally, slowly add 4-dimethylaminopyridine (DMAP) powder (6.1 g, 0.05 mol) and stop the reaction after 8 h. The insoluble matter was filtered off, and the filtrate was taken into a separatory funnel and extracted with water. The organic layers were combined and dried over anhydrous Na2SO4. The filtrate was spin-dried to obtain a red viscous liquid. After standing and cooling, a small amount of solid precipitated, which was filtered again to obtain the final product BMI-600E.
[0037] The product was characterized by hydrogen NMR spectrum, and its NMR data are as follows: 1H NMR (500 MHz, Chloroform-d)δ 6.64 (s, 4H), 5.78 – 5.65 (m, 2H), 5.61 (dtt, J = 15.2, 5.7, 0.8 Hz, 1H), 5.55 – 5.43 (m, 2H), 5.05 (tdd, J = 15.9, 2.2, 1.0 Hz, 2H), 4.59 (dp, J =4.2, 1.0 Hz, 2H), 4.29 (qd, J = 11.4, 3.2 Hz, 2H), 4.16 – 3.97 (m, 4H), 3.74(dt, J = 4.6, 3.2 Hz, 1H), 3.62 (q, J = 4.5 Hz, 1H), 3.12 (q, J = 4.6 Hz,1H), 3.05 (q, J = 4.5 Hz, 1H), 2.80 – 2.62 (m, 4H), 2.34 – 2.19 (m, 1H), 2.16– 1.99 (m, 6H), 1.77 – 1.69 (m, 2H), 1.69 – 1.57 (m, 4H), 1.55 – 1.42 (m, 2H).
[0038] Preparation Example 2
[0039]
[0040] Maleimidocaproic acid (315 g, 1.5 mol) was dissolved in 2500 mL of dichloromethane, and then dicyclohexylcarbodiimide (DCC) powder (309 g, 1.5 mol) was dissolved in 300 mL of dichloromethane. Under stirring, the DCC solution was slowly added to the maleimidocaproic acid solution. After all the additions were completed, the stirring reaction was continued for 10 min. Then (epoxidized polybutadiene, Total) Polybd 600E (725 g, 0.5 mol) was added to the system; finally, 4-dimethylaminopyridine (DMAP) powder (6.1 g, 0.05 mol) was slowly added, and the reaction was stopped after 8 h. The insoluble matter was filtered out, and the filtrate was extracted with water in a separatory funnel. The organic layers were combined and dried over anhydrous Na2SO4. The filtrate was spun dry to obtain a red viscous liquid. After standing and cooling, a small amount of solid precipitated, and it was filtered again to obtain the final product. 1H NMR (500 MHz, Chloroform-d) δ 6.71 (s, 4H), 5.78– 5.65 (m, 2H), 5.64 – 5.57 (m, 1H), 5.54 – 5.42 (m, 2H), 5.05 (tdd, J =16.0, 2.2, 1.0 Hz, 2H), 4.59 (ddt, J = 4.2, 1.8, 0.9 Hz, 2H), 4.28 (qd, J =11.5, 3.2 Hz, 2H), 3.75 (dt, J = 4.4, 3.2 Hz, 1H), 3.70 – 3.58 (m, 5H), 3.12(q, J = 4.6 Hz, 1H), 3.05 (q, J = 4.5 Hz, 1H), 2.36 – 2.28 (m, 4H), 2.29 –2.20 (m, 1H), 2.13 – 2.00 (m, 6H), 1.78 – 1.56 (m, 15H), 1.54 – 1.43 (m, 2H),1.43 – 1.34 (m, 4H).
[0041] Comparative Example 1
[0042] BMI-PPG400 disclosed in CN117844435A was used as comparative compound 1.
[0043] Comparative Example 2
[0044] BMI-PPG1000 disclosed in CN117844435A was used as comparative compound 2.
[0045] The test method involved in the present invention is as follows:
[0046] (1) Volume resistivity test:
[0047] Refer to the four-probe method of the industry standard "HG / T 5912-2021 Conductive Adhesives".
[0048] Preparation of conductive film: On a glass substrate, a conductive film with a thickness of ~25 μm, a width of 9 mm, and a length of 50 mm was prepared by a controlled thickness tape scraping method.
[0049] Curing conditions: The test piece was placed in an oven and heated from 25 o C to 175℃, and then keep at 175℃ for 60 min.
[0050] Test equipment: TH2516 DC resistance tester from Changzhou Tonghui Electronics Co., Ltd.
[0051] (2) Storage modulus:
[0052] Use a mold to prepare a conductive adhesive cured sample of 15mm×3mm×1.5mm (length×width×thickness).
[0053] Curing conditions: The test piece was placed in an oven and heated from 25 o C to 175℃, and then keep at 175℃ for 60 min.
[0054] The test adopts the tensile mode, with a maximum load of 1N; frequency of 1Hz, temperature range: 0℃~250℃, and heating rate: 2℃ / min.
[0055] Test equipment: DMA 861 Dynamic Mechanical Analyzer (Mettler Toledo).
[0056] (3) Chip thrust:
[0057] The test method refers to "HG / T 5912-2021 Conductive Adhesives".
[0058] The size of the silicon wafer is: 2 mm × 2 mm (thickness 500um); the substrate is a silver-plated copper sheet.
[0059] Curing conditions: The test piece was placed in an oven and heated from 25 o The temperature was raised from 175°C to 175°C, and then kept at 175°C for 60 min. The testing equipment was a DAGE-4000P multifunctional push-pull testing machine (Nordson DAGE Precision Industries LTD, USA) with a temperature-controlled heating table. The shear strength was the thrust force (in kgF, kilogram-force). Ten test data were taken from the test samples corresponding to each type of glue, and the arithmetic mean of the results was taken.
[0060] When measuring high-temperature thrust, set the temperature on the temperature-controlled heating platform, wait for the target temperature to be reached and stabilize for 5 minutes before starting to measure the thrust.
[0061] (4) Residual glue rate on broken ring surface:
[0062] Destruction surface evaluation: After the chip thrust test is completed, the substrate is placed on the microscope stage and the residual glue on the substrate after the thrust damage is observed through an optical microscope. The residual glue area ratio (percentage relative to the chip area) is evaluated for assessment. The score is based on a 10-point system, 100% residual glue corresponds to 10; 90% residual glue corresponds to 9, and so on. 10% residual glue corresponds to 1; 0% residual glue corresponds to 0; the arithmetic average of 10 samples is taken.
[0063] Testing equipment: Shanghai Optical Instrument Factory-6XM-PC metallographic microscope. The higher the residual glue rate, the better the bonding performance.
[0064] (5) Chip warping:
[0065] The silver-plated frame is used, the chip size is 9 mm×9 mm, and the chip / frame is baked and cured in an oven after the glue is applied by drawing lines. Curing conditions: The test piece is placed in an oven and heated from 25°C / min to o The temperature was raised to 175°C, and then kept at 175°C for 60 min. The warpage was obtained by measuring the surface roughness along the diagonal direction of the chip. The unit was μm. A value less than 20 μm was considered passed, while a value exceeding 20 μm was considered unqualified.
[0066] Test equipment: KEYENCE VHX-970FN digital microscope system.
[0067] (6) Comparison of thermal stability: using thermogravimetric analysis method.
[0068] The heat resistance of BMI-PPG400, BMI-PPG1000 and BMI-600E was compared by TGA thermogravimetric analysis (the test equipment was TGA( / DSC3+) thermogravimetric analyzer from Mettler Toledo, Switzerland). 25℃~500℃ Heating rate: 10℃ / min, see Figure 1 .
[0069] pass Figure 1 Thermogravimetric analysis shows that BMI-600E (Preparation Example 1) has better thermal stability than BMI-PPG1000, and it does not thermally decompose until 380°C to lose 8% of its mass, while the latter thermally decomposes at 327°C to lose 12% of its mass.
[0070] The raw materials involved in the preparation of conductive adhesive are shown in Table 1 below.
[0071] Table 1
[0072]
[0073] (Take reference example 1 as an example):
[0074] Weigh 10 parts by mass of epoxy resin 835LV, 3 parts by mass of BMI-PPG400, 9 parts by mass of acid anhydride MeTHPA, 0.1 parts by mass of isopropylbenzene hydroperoxide (CHPO), 0.2 parts by mass of silane coupling agent KH-560, and 0.1 parts by mass of 2E4MZ-CN, add them into a mixing kettle, mix at 800 rpm for 15 min, add 3 times the mass of silver powder EA-029 (the total mass of other materials except silver powder), disperse at 800 rpm for 15 min, degas under vacuum (vacuum degree <-0.095 MPa) for 10 min, and discharge under normal pressure to obtain a conductive adhesive.
[0075] Reference Example 2 provides a conductive adhesive, wherein the compound BMI-PPG400 in Reference Example 1 is replaced with an equal amount of BMI-PPG1000, and other raw material components and amounts are shown in Table 2. The preparation method is the same as that of Reference Example 1.
[0076] Application Example 1 provides a conductive adhesive, wherein the compound BMI-PPG400 in Reference Example 1 is replaced with an equal amount of BMI-600E, and other raw material components and amounts are shown in Table 2. The preparation method is the same as that of Reference Example 1.
[0077] The composition and performance test results of Reference Example 2 and Application Example 1 are shown in Table 2 below.
[0078] Table 2
[0079]
[0080] Data Discussion:
[0081] Compared with reference examples 1 and 2, application example 1 has a lower volume resistivity (better conductivity) after curing of the conductive adhesive prepared under the same content, and the chip thrust at room temperature and high temperature is significantly improved, and the residual adhesive rate of the residual adhesive surface after destruction is equivalent, and the chip warping is less than 20um. This shows that Example 1 has good bonding performance with the silver-plated substrate. In addition, the storage modulus test results show that the modulus of Example 1 at room temperature after curing is lower than that of the reference example. The lower the modulus, the smaller the internal stress under the same strain, which is more conducive to improving reliability and less prone to cracking or delamination.
[0082] The applicant declares that the present invention illustrates the bismaleimide resin and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A bismaleimide resin, characterized in that The bismaleimide resin has a structure as shown in Formula 1: ; Formula 1 Wherein, R1 is selected from C1-C5 alkylene, and the number average molecular weight of the bismaleimide resin is 2000g / mol-3000g / mol.
2. The bismaleimide resin according to claim 1, characterized in that R1 is selected from -CH2-, -CH2-CH2- or -CH2-CH2-CH2-CH2-CH2-CH2-.
3. The bismaleimide resin according to claim 1, characterized in that The bismaleimide resin is selected from any one of the following resins: ; 。 4. The method for preparing the bismaleimide resin according to claim 1, wherein The preparation method comprises the following steps: The compound represented by formula A reacts with the compound represented by formula B to obtain the bismaleimide resin represented by formula 1. The reaction formula is as follows: ; Wherein, R1 is selected from C1-C5 alkylene, and the number average molecular weight of the bismaleimide resin is 2000g / mol-3000g / mol.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the compound represented by formula A to the compound represented by formula B is 3:1-6:
1.
6. The preparation method according to claim 4, characterized in that: The reaction is carried out in the presence of a dehydrating agent; The molar ratio of the compound represented by formula A to the dehydrating agent is 1:1-1:2; The dehydrating agent is selected from at least one of N,N'-dicyclohexylcarbodiimide, diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.
7. The preparation method according to claim 4, characterized in that: The reaction is carried out in the presence of a catalyst; The catalyst is selected from at least one of 4-dimethylaminopyridine, 4-pyrrolidinylpyridine, hydroxybenzotriazole or diphenylamine trifluoromethanesulfonate; The molar ratio of the catalyst to the compound represented by formula B is 1:10-1:
15.
8. The preparation method according to claim 4, characterized in that: The reaction temperature is room temperature and the reaction time is 12-24 hours.
9. Use of the bismaleimide resin according to any one of claims 1 to 3 in the preparation of thermosetting materials.
Citation Information
Patent Citations
Cyanate ester composition containing BMI resin and application
CN117844435A
Modified polybutadiene prepolymer as well as preparation method and application thereof
CN107033517A
Resin composition for forming electrodes, chip electronic component and method for producing same
CN110462752A